THE EFFECTIVENESS OF USING AUDIOVISUAL LEARNING MEDIA TO IMPROVE BASIC ATHLETIC MOVEMENT SKILLS IN CLASS VIII-1 STUDENTS AT SMP 13 BANDA ACEH - Intan Vida Yasasi; Alief Akbar; Ruslan; Mansur (CV. Asry Persada Quality, 2025)
This Classroom Action Research (CAR) aims to test the effectiveness of using audiovisual learning media in improving basic athletic movement skills in class VIII-1 students at SMP 13 Banda Aceh. This research is motivated by the low basic athletic movement skills of students, which can have an impact on their physical development and sports abilities. In this study, audiovisual media is used as a means to provide a clear visual description of the correct basic athletic movement techniques. The results of the study showed a significant increase in students' basic athletic movement skills after the application of audiovisual media. This study is expected to be a reference for improving the quality of sports learning in schools.